Bank exposures and sovereign stress transmission - Carlo Altavilla; Marco Pagano; Saverio Simonelli (European Central Bank (ECB), 2016)
Using novel monthly data for 226 euro-area banks from 2007 to 2015, we investigate the determinants of changes in banks' sovereign exposures and their effects during and after the euro crisis. First, the publicly owned, recently bailed out and less strongly capitalized banks reacted to sovereign stress by increasing their domestic sovereign holdings more than other banks, suggesting that their choices were affected both by moral suasion and by yield-seeking. Second, their exposures significantly amplified the transmission of risk from the sovereign and its impact on lending. This amplification of the impact on lending does not appear to arise from spurious correlation or reverse causality.
Keywords: E44; F3; G01; G21; H63; 330; credit risk; diabolic loop; euro debt crisis; sovereign exposures; sovereign risk